2015
DOI: 10.1186/s12986-015-0019-0
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity measures and vitamin D concentrations in Northeast Germany and Denmark

Abstract: BackgroundBody mass index (BMI) and serum 25-hydroxy vitamin D3 (25OHD) concentrations are inversely related. As BMI contains only limited information regarding body fat distribution, we aimed to analyze the cross-sectional associations of abdominal visceral or subcutaneous adipose tissue, next to common adiposity measures, with the 25OHD concentration.MethodsData were obtained from three cohorts of two large epidemiological studies in the northeast of Germany (Study of Health in Pomerania, SHIP-1 and SHIP-Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
4
23
0
Order By: Relevance
“…Next to common adiposity measures, we also discovered that VFA was inversely associated with serum 25(OH) D 3 concentrations in Chinese men and pre-menopausal women, which was similar to the recent study in Northeast Germany and Denmark [ 38 ] and China [ 16 ]. Differed from Hao’s study among Chinese population, our study population included men and women, and included the participants who were diabetes.…”
Section: Discussionsupporting
confidence: 86%
“…Next to common adiposity measures, we also discovered that VFA was inversely associated with serum 25(OH) D 3 concentrations in Chinese men and pre-menopausal women, which was similar to the recent study in Northeast Germany and Denmark [ 38 ] and China [ 16 ]. Differed from Hao’s study among Chinese population, our study population included men and women, and included the participants who were diabetes.…”
Section: Discussionsupporting
confidence: 86%
“…In another study, a significant negative correlation was found between body fat and vitamin D serum levels [ 45 ]. In this sense, a cross-sectional study showed that weight, body fat mass, and BMI were negatively correlated to 25(OH)D levels [ 46 ], as well as WC and other obesity markers [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…VAT was the distance in centimeters between the posterior edge of the abdominal muscles and the front of the lumbar spine. 27,28 All ultrasound measures were performed after a quiet expiration applying minimal pressure without the displacement of the intra-abdominal contents as described by Stolk et al 17 with an Aquila Pie Medical, Esaote Europe, Maastricht, The Netherlands. These ultrasound measures have been validated against CT and MRI elsewhere.…”
Section: Exposure Measurementsmentioning
confidence: 99%